2016
DOI: 10.1002/ajh.24499
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of pneumocystis pneumonia utilizing PCR‐based diagnosis in patients with B‐cell lymphoma receiving rituximab‐containing combination chemotherapy

Abstract: Recent literature has demonstrated concern over the risk of Pneumocystis jirovecii pneumonia (PJP) when administering rituximab with combination chemotherapy such as in R-CHOP; however, the exact risk and potential need for prophylaxis is unknown. We sought to determine the incidence of PJP infection following R-CHOP administration in patients with B-cell lymphoma. Consecutive patients diagnosed with B-cell lymphoma receiving R-CHOP were evaluated from chemotherapy initiation until 180 days after the last admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…Thus, when rituximab is administered for various diseases, regular pneumocystis prophylaxis with TMP/SMX is widely recommended by many treatment guidelines, such as Wegener’s granulomatosis and organ or haematopoietic transplant 15 , 16 . However, the necessity of pneumocystis prophylaxis for HIV-uninfected, rituximab-treated non-Hodgkin lymphoma (NHL) patients remains controversial because the benefits and risks of prophylaxis have not been assessed in a large-scale study 4 , 10 , 17 . Thus, in this report, we investigated the beneficial effect of pneumocystis prophylaxis with oral TMP/SMX in HIV-uninfected NHL patients by analysing data from a national registry, the Taiwan National Health Insurance Research Database (NHIRD).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when rituximab is administered for various diseases, regular pneumocystis prophylaxis with TMP/SMX is widely recommended by many treatment guidelines, such as Wegener’s granulomatosis and organ or haematopoietic transplant 15 , 16 . However, the necessity of pneumocystis prophylaxis for HIV-uninfected, rituximab-treated non-Hodgkin lymphoma (NHL) patients remains controversial because the benefits and risks of prophylaxis have not been assessed in a large-scale study 4 , 10 , 17 . Thus, in this report, we investigated the beneficial effect of pneumocystis prophylaxis with oral TMP/SMX in HIV-uninfected NHL patients by analysing data from a national registry, the Taiwan National Health Insurance Research Database (NHIRD).…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia was previously reported during rituximab treatment; it is thought to be induced by B-cell deficiency or a yet undetermined mechanism of rituximab. [ 12 , 13 ] No new adverse reactions were observed in this case. The pneumonia improved after antibiotics treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Individual studies and a systematic review and meta-analysis using various databases have demonstrated a low overall incidence of PJP in the setting of rituximab-inclusive treatments. [35][36][37] Due to the retrospective nature of this work, it is impossible to determine if this finding represents selection bias by providers who may have been less inclined to prescribe aggressive, intensive combination chemotherapy to patients with comorbid conditions and a Univariate analysis incorporating steroids into chemotherapy was impossible as it would include nearly every patient in our cohort and the low overall incidence of PJP in our patient cohort precluded multivariable analysis to assess if there was additional risk conferred by any particular bendamustinebased combination regimen. Agents commonly used for prophylaxis have considerable adverse event profiles.…”
Section: Discussionmentioning
confidence: 99%